Electrochemical Performance of Galvanic Cell with Silver Coated Cathode in One Compartment System Using Seawater as Electrolyte - Gurum Ahmad Pauzi; Ahmad Saudi Samosir; Sri Ratna Sulistiyanti; Wasinton Simanjuntak (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
This research was carried out to evaluate the electrochemical performance of a galvanic cell using seawater as an electrolyte. The cell was designed to have a volume of 200 mL and equipped with Zn as an anode and Ag-coated Cu as a cathode (Cu(Ag)-Zn system) in order to suppress the corrosion of Cu. As a comparison, the same experiment with the use of uncoated Cu as a cathode (Cu-Zn system) was also conducted. To conduct the experiment, a system was assembled by connecting 20 cells in series and placed in a closed container filled with seawater. The experiment was run for 72 hours, divided into three 24-hour cycles, by replacing the seawater every 24 hours. The performance of the system was evaluated in terms of open circuit voltage, close circuit voltage, current, light intensity, internal resistance, and power. The experimental results show that the corrosion rate of Cu coated with silver was smaller than that of uncoated Cu. Compared to the performance of the Cu-Zn system, it was also found that the Cu(Ag)-Zn system produced higher power and light intensity, which is in accordance with its smaller internal resistance. The overall experimental results indicate better performance of Cu(Ag)-Zn system and this better performance is attributed to the significantly lower corrosion rate of Cu(Ag) cathode which signifies the role of Ag layer to protect the Cu from attack by seawater. As a result, the Cu(Ag)-Zn system maintained the cathode corrosion rate with a ratio of 0.19. The percentage decrease of the OCV of the Cu(Ag)-Zn system was 6.14%, the CCV on the third day was 0.99%, the current was 36.68%, and the power was 37.83%.